Effect of chronic exercise on fluoride metabolism in fluorosis-susceptible mice exposed to high fluoride - Amaral, Sandra L. [UNESP]; Azevedo, Liane B.; Buzalaf, Marilia A. R.; Fabricio, Mayara F. [UNESP]; Fernandes, Mileni S.; Valentine, Ruth A.; Maguire, Anne; Zohoori, Fatemeh V. (Nature Publishing Group, 2018)
The present study investigated the effect of chronic exercise on fluoride (F) metabolism in fluorosis-susceptible mice exposed to high-F and explored the relationship between F concentrations in bone and plasma. Thirty male mice were randomised into three groups: Group I (No-F, No-Exercise), Group II (50 ppmF, No-Exercise), Group III (50 ppmF, Exercise). Body weight and physical performance of all mice were measured at baseline and end of experiment. F concentrations of plasma and bone were measured at the end of experiment. Mean plasma F concentration was significantly higher (p < 0.001) in Groups II and III compared with Group I. Mean bone F concentration was also significantly higher (p < 0.01) in Groups II and III compared with Group I. There was a significant correlation (p = 0.01, r = 0.54) between F concentration of plasma and bone. Mean body weight of Group I mice was significantly higher than Group II (p < 0.001) and Group III (p = 0.001) mice at the end of the experiment. This study, which provides the first data on the effect of chronic exercise on F metabolism in fluorosis-susceptible mice, suggests no effect of chronic exercise on F in plasma and bone. However, exposure to high-F resulted in lower body weight and exercise capacity in mice.